The Factor Model of Decentralization and Quality of Governance in European Union - Jože Benčina; Anja Mrđa Kovačič (Central European Public Administration Review)
This paper presents a selection of 43 variables collected from various sources, which are used to describe the concepts of decentralization and quality of governance in the EU countries. Decentralization is analyzed from two aspects, fiscal and political, while the quality of governance is, along with certain real indicators, measured in particular with the opinions of citizens. The aim of the research was to determine the factor structure of selected variables and provide guidelines for using best practices in exploratory factor analysis. The exploratory factor analysis classified the selected variables into three factors of fiscal decentralization (Fiscal decentralization, Fiscal centralization and Government expenditure), three factors of political decentralization (Centripetalism, Regional governance, Federalism) and three factors of quality of governance (Quality of European institutions, Quality of national institutions and Enforcement of EU law). Despite the small population observed, the factors showed quite good characteristics and provided a good starting point for further research. In this manner, it was shown that despite a small population, it is possible to develop factor models of suitable quality by using exploratory factor analysis in the sense of best practices.